Centrality in networks of geographically proximate firms and competitive capabilities - Bárbara Larra\~neta; F. Xavier Molina-Morales; Ines Herrero (BRQ Business Research Quarterly, 2020)
We examine how a firm's centrality within a network of geographically proximate firms affects its competitive capabilities. Our study of the total population of one Spanish cluster of fishing firms shows that the effects of centrality on a firm's competitive capabilities are contingent on the effects of two relational characteristics of its direct ties: strength and degree of cognitive cohesion. Specifically, our results indicate that the centrality of a firm within the cluster network enhances its competitive capabilities as the strength of its direct ties increases. Furthermore, firms can capture the value of centrality for enhancing competitive capabilities with a combination of strong (or weak) direct ties and low (or high) degree of cognitive cohesion. We contribute to the network and strategy literatures by reconciling conflicting results with regard to the strategic benefits of a firm's centrality in a cluster and the relational characteristics of its direct ties.
Keywords: L14; M1; Q22; R10; 650; Competitive capabilities; regional clusters; knowledge networks; network centrality; tie strength; tie cognitive cohesion